The museum of natural history. - Benjamin, Walter; Green, Renée; Parson, Laurie; Samore, Sam; Stockholder, Jessica; Winer, Andrew (Amsterdam : Galerie Barbara Farber, 1991)
Ball, Barry X ; Faust, Gretchen ; Fehlau, Fred ; Gonzalez-Torres, Felix ; Green, Renée ; Lum, Ken ; McCaslin, Matthew ; Noland, Cady ; Parsons, Laurie ; Samore, Sam ; Stockholder, Jessica ; Williams, Christopher ; Wool, Christopher
The museum of natural history, Galerie Barbara Farber, Amsterdam, 27 april - 15 juni 1991
Engels
boek